The Strange Death of Lutheran England - Ryrie, Alec (The journal of ecclesiastical history, 2002)
A Lutheran settlement was the natural outcome for a politically imposed Reformation such as that of Henry VIII. Some aspects of his settlement pointed in that direction, and English evangelicalism during his reign leaned more towards Lutheranism than has been hitherto appreciated. Reformed views only came to dominate the movement at the very end of the reign. This shift reflects the waning influence of German Lutheranism in England, and arguably also the influence of Lollard sacramentarianism. Henry VIII's radical attitude towards images also brought some quasi-Reformed ideas into his settlement. Most important, from 1543 onwards the regime drove Lutheran-leaning evangelicals into open opposition, forcing them towards more confrontational Reformed doctrines.